2014
DOI: 10.3109/13813455.2014.928731
|View full text |Cite
|
Sign up to set email alerts
|

L-Carnitine supplementation impairs endothelium-dependent relaxation in mesenteric arteries from rats

Abstract: L-Carnitine (L-Car) is taken as fat burner. The risks of L-Car supplementation for the cardiovascular system are unclear. We evaluated the relaxing responses of the mesenteric and aorta rings from rats after four weeks of L-Car supplementation and/or physical training. Concentration response curves to acetylcholine (ACh) and sodium nitroprusside (SNP), as well as cyclic GMP levels, superoxide dismutase (SOD) activity and malondialdehyde (MDA) were evaluated. Physical training decreased body weight gain that wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The improvement in vascular reactivity, represented by the reduction in the contractile activity (Delbin et al, 2012 ; Okudan et al, 2012 ) and increased relaxing activity (Valgas Da Silva et al, 2014 ) is already well established for the aerobic exercise modality. Concerning the role of strength training in vascular reactivity, three studies have demonstrated improvement in relaxing activity (Figard et al, 2006 ; Harris et al, 2010 ; Araujo et al, 2013 ) and only in one of them the contractile reactivity with a reduction in this activity was measured (Araujo et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The improvement in vascular reactivity, represented by the reduction in the contractile activity (Delbin et al, 2012 ; Okudan et al, 2012 ) and increased relaxing activity (Valgas Da Silva et al, 2014 ) is already well established for the aerobic exercise modality. Concerning the role of strength training in vascular reactivity, three studies have demonstrated improvement in relaxing activity (Figard et al, 2006 ; Harris et al, 2010 ; Araujo et al, 2013 ) and only in one of them the contractile reactivity with a reduction in this activity was measured (Araujo et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“… 46 48 However, in rats supplemented with L-carnitine, which has antioxidant properties, we have found impaired endothelium-dependent relaxation in mesenteric artery of sedentary and trained lean rats, corroborating our data that exogenous antioxidants may occasionally impair vasodilation. 49 , 50 It is well known that several antioxidants derived from plants and fruits improve endothelial and vascular function by decreasing oxidative stress. 51 However, since NO is a free radical, antioxidants may also scavenge NO.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular relaxation was expressed as the percentage of PE-induced maximum contraction. Potency is given by the pEC 50 which represents the concentration of each drug necessary to cause 50% of maximum relaxation, and it was expressed as −log molar (mol/L). ACh, SNP and PE were purchased from Sigma-Aldrich Co. (St Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%